Hydroxylation Kinetics of Epoxidized Tung Oil Using Methanol as Nucleophilic Agent - Budiyati, Eni; Rochmadi, Rochmadi; Budiman, Arief; Budhijanto, Budhijanto (Faculty of Engineering, Universitas Indonesia, 2023)
The synthesis of vegetable oil-based polyols has been carried out through the epoxidation-hydroxylation process. However, Tung oil has never been explored in the process, even though Tung oil has a high double bond. Epoxidized Tung Oil (ETO) with oxirane numbers of 3.92 to 4.04 mmol/g were hydroxylated with methanol and catalyzed by Sulfuric Acid (H2SO4). The objective of this study is to produce polyols from ETO and to evaluate the influence of temperature and catalyst concentration on the hydroxylation process. A second-order reaction kinetic study was also developed to represent the reaction. The ETO hydroxylation was carried out in a batch reactor for four hours. The reaction rate was determined based on the concentration of ETO (oxirane number) and Hydroxyl Value (OHV). The result shows that temperature and catalyst concentration have a directly proportional correlation to OHV and are inversely proportional to the concentration of ETO (epoxy). For temperatures above 40Â°C, the decreasing rate of the epoxy concentration at the beginning was relatively much faster than at the end of the reaction. In the temperature variation, the highest OHV obtained was 3.70 mmolKOH/g or 207.39 mgKOH/g at 80Â°C. The optimum catalyst concentration obtained in this study was 3%. The evaluated kinetics model gave great results for all reaction temperatures, with the highest total SSE for epoxy concentration and OHV data fitting of 0.156 and 0.045, respectively. The calculated activation energy (Ea) was 30.41 kJ/mol and the pre-exponential factor (A) was 255.00 g.mmol-1.min-1.